Electrochemical Reduction Behaviour and Analysis of Fluazinam - K.BALAJI; C.SRIDEVI; N.ANANDA KUMAR REDDY; K.MOHANA MUNI SIDDA REDDY; C.SURESH REDDY (International Journal of Pharma and Bio Sciences, 2010)
The electrochemical reduction behaviour of Fluazinam has been studied by employing dc polarography, cyclic voltammetry, ac polarography and differential pulse polarography in Britton-Robinson buffer of pH ranging from 2.0 to 12.0. A differential pulse polarographic method is described for the determination of Fluazinam in various environmental matrices by using standard addition and calibration methods. The kinetic parameters such as diffusion coefficients (D) and heterogeneous forward rate constants (K0f.h) values are evaluated using these techniques.